Association between intraoperative dexmedetomidine and all-cause mortality and recurrence after laparoscopic resection of colorectal cancer: Follow-up analysis of a previous randomized controlled trial - Hu, Jingping; Gong, Chulian; Xiao, Xue; Chen, Liubing; Zhang, Yihan; Li, Xiaoyue; Li, Yanting; Zang, Xiangyang; Huang, Pinjie; Zhou, Shaoli; Chen, Chaojin (Frontiers in Oncology, 2023)
Background: Dexmedetomidine (DEX) has been widely applied in anaesthesia and sedation of patients with oncological disease. However, the potential effect of DEX on tumour metastasis remains contradictory. This study presents a 5-year follow-up of patients receiving intraoperative DEX in laparoscopic resection of colorectal cancer of a previous randomized clinical trial. Methods: 60 patients undergoing laparoscopic colorectal resection between June 2015 and December 2015 were randomly assigned into DEX group and Control group. In DEX group, initial dose of DEX was loaded (1μ/kg) before induction for 10 minutes followed by continuous infusion (0.3μg/kg/h) during surgery and the patients in Control group were given the same volume of saline. A 5-year follow-up analysis was conducted to evaluate the overall survival, disease-free survival and tumour recurrence. Results: 55 of the 60 patients were included in the follow-up analysis. 28 patients were in the DEX group and 27 patients were in Control group. Baseline characteristics were comparable between the two groups, except for vascular and/or neural invasion of the tumour in the DEX Group (9/28 vs. 0/27, P = 0.002). We did not observe a statistically significant benefit but rather a trend towards an increase in overall survival and disease-free survival in the DEX Group, 1-year overall survival (96.4% vs. 88.9%, P = 0.282), 2-year overall survival (89.3% vs. 74.1%, P = 0.144), 3-year overall survival (89.3% vs. 70.4%, P = 0.08), and 5-year overall survival (78.6% vs. 59.3%, P = 0.121). The total rates of mortality and recurrence between the two groups were comparable (8/28 vs. 11/27, P = 0.343). Conclusion: Administration of DEX during laparoscopic resection of colorectal cancer had a non-significant trend towards improved overall survival and disease-free survival. Registration number: ChiCTRIOR-15006518